Rancang Bangun Sistem Informasi Manajemen Aset Inventaris Berbasis Web Dengan Menggunakan Model Waterfall (Studi Kasus : SMPN 02 Cisoka) - Rafi Apriyana; Fajar Septian (CV. Multi Kreasi Media, 2023)
The development in the field of information technology has a very big influence in the world of work, especially in the field of management, old systems are starting to be replaced by new systems which are the result of increasingly advanced technological developments . One of them is the use of a management information system which is a must in an agency, which is generally used to process data into an accurate information to improve performance in order to more effectively and efficiently so as to support the purpose of the agency that in making a decision. To provide maximum service, in a space sphere schools need no activity management of assets as one of the main activities that deal with issues of procurement type of asset in supporting the needs of operational school . For management of assets in SMPN 2 Cisoka as long as it is still done manually without having to do management in it that give rise to various problems such as when recording an asset that causes detail the assets held is not clear. Based on the above services have been properly made system of information management of assets as one of the alternatives to improve the performance of the administration in SMP Negeri 2 Cisoka. With the made system of information management asset, the processing of existing assets in SMPN 2 Cisoka will be arranged by effectively and efficiently, the data amount of assets will be seen moreclearly.